Health educational practices in the multidisciplinary context: experience report (Research, Society and Development, 2021)
Introduction: The training of professionals, focused on the Unified Health System (SUS), has been a relevant topic in health education, thus boosting the training of the professionals for a differentiated performance. In this sense, the Multiprofessional Residency Program in Family Health (PRMSF) is supported by the process of teaching, learning and professional practice in loco. The educational practices, through integrative seminars, articulate contents from different areas of knowledge and provide an exchange of experience between the professionals involved. Objectives: Report the contributions of educational practices developed in the form of seminars. Methodology: This is a qualitative study with a descriptive-reflective approach, experience report type, based on the execution of face-to-face and virtual seminars, developed based on the experience of organizing and participating in seminars developed by PRMSF residents, allied with the Municipal Public Health School, in the municipality of Cascavel/PR. Results and discussion: Working on content aimed at professional practice, by conducting seminars, stimulates the process of integration and closer relations between residents, preceptors, instructors and health workers, proposing reflections on the work process contributing to quality care.  Conclusion: The seminars stand out as an alternative to carrying out educational practices in health, allowing the articulation of several professionals simultaneously, for collective construction of knowledge, in order to meet the principles and guidelines of the SUS. The importance of continuity of the seminars plan is pointed out, following up on the critical-reflectives analysis generated.